Volumetric Modulated Arc Therapy versus Intensity Modulated Radiation Therapy in the Treatment of Prostate Cancer: A Systematic Literature Review - Issam Lalya; Noha Zaghba; Khalid Andaloussi-Saghir; Mohamed Elmarjany; Laila Baddouh; Keltoum Dahmani; Khalid Hadadi; Hassan Sifat; Hamid Mansouri (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2016)
Aim: Provide evidence concerning advantages of volumetric modulated arc therapy over intensity modulated radiation therapy. Background: External beam radiation therapy is a major treatment modality of prostate cancer; especially in high and intermediate risk categories in combination with androgen deprivation therapy.The  advent  of  new  techniques of irradiation such as intensity modulated radiation therapy (IMRT) improved significantly the biochemical free survival by allowing dose escalation without enhancement of  related  toxicities.Volumetric modulated  arc  therapy  (VMAT)  is  a  circular  technique  delivering radiation dose using one or multiple arc of 360° around the target volumes. Methods: We  collected  all  dosimetric  studies  comparing  VAMT  versus  IMRT,  published  in PubMed  indexed  journals  between  2008  and  2015.  Parameters  of  comparison  were  dose  volume histograms for target volumes and organs at risk, number of monitors units and treatment time. Results: Globally, the target volumes coverage and organ at risk protection were similar between the two techniques. VMAT has the advantage to reduce significantly the number of monitor units and treatment time. Conclusion: VMAT is a very efficient technique of radiation therapy, and should be preferred in the treatment of prostate cancer.